2023
DOI: 10.3390/cancers15164162
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Radiological Evaluation of and Theranostics for Glioblastoma

Grayson W. Hooper,
Shehbaz Ansari,
Jason M. Johnson
et al.

Abstract: Imaging is essential for evaluating patients with glioblastoma. Traditionally a multimodality undertaking, CT, including CT cerebral blood profusion, PET/CT with traditional fluorine-18 fluorodeoxyglucose (18F-FDG), and MRI have been the mainstays for diagnosis and post-therapeutic assessment. However, recent advances in these modalities, in league with the emerging fields of radiomics and theranostics, may prove helpful in improving diagnostic accuracy and treating the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In addition to exhibiting overexpression in prostate cancer, this antigen has also been identified in the highly vascularized endothelium of other tumors, most notably glioblastomas. Recent studies have demonstrated the effectiveness of 68 Ga-PSMA PET imaging of gliomas due to the high tumor-to-brain ratio (TBR) of this radiotracer [24]. One theranostic partner for 68 Ga-PSMA is 177 Lu-PSMA-617, a beta-emitting compound containing lutetium that similarly uses PSMA as its target molecule, delivering radiation to the PSMA-expressing tumor cells [25].…”
Section: Theranostic Use In Gliomasmentioning
confidence: 99%
“…In addition to exhibiting overexpression in prostate cancer, this antigen has also been identified in the highly vascularized endothelium of other tumors, most notably glioblastomas. Recent studies have demonstrated the effectiveness of 68 Ga-PSMA PET imaging of gliomas due to the high tumor-to-brain ratio (TBR) of this radiotracer [24]. One theranostic partner for 68 Ga-PSMA is 177 Lu-PSMA-617, a beta-emitting compound containing lutetium that similarly uses PSMA as its target molecule, delivering radiation to the PSMA-expressing tumor cells [25].…”
Section: Theranostic Use In Gliomasmentioning
confidence: 99%
“…Recent studies have also shown increasing interest in some neuroradiological parameters, evaluated both prior and after surgery, that seem to play a predictive role in overall survival (OS) and progression-free survival (PFS) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Radiologists strive to identify the predominant component of the lesion to determine prognostic factors and categorize the findings according to the RANO criteria, thus providing the most appropriate treatment for the patient. To overcome the aforementioned limitations in the follow-up, incorporating changes measured by advanced MRI and positron emission tomography (PET) imaging, which may precede anatomical changes in tumor volume, shows promise [ 55 , 56 ]. PET may also help to differentiate actual progression from pseudo progression [ 57 ].…”
Section: Introductionmentioning
confidence: 99%